Internalization of Islamic Teachings in Islamic Boarding School-Based Educational Institutions in Forming Religious Graduates - Ahmad Zubaidi Zubaidi; Fitrotul Kamilah (Jurnal Evaluasi dan Pembelajaran, 2023)
The process of unifying values in one's self through appreciation, understanding, instilling, and fostering a value, attitude, teaching or belief from the surrounding environment then blends and becomes knowledge that influences one's life then is reflected in his daily behavior which is carried out intensively and continuously with the aim of always maintaining Islamic teachings, especially for students and graduates. This study used a qualitative descriptive approach, data collection techniques using interviews, observation, and documentation which were analyzed descriptively. While the data analysis used is data reduction, data presentation, and drawing conclusions. The results of this study indicate that the internalization of Islamic teachings in Islamic boarding schools-based educational institutions in forming religious graduates starts from the process of planning, organizing, implementing, and evaluating or supervising. This is in line with the support from the resources involved from the school by using learning strategies, habituation, and punishment. The supporting and inhibiting factors for the internalization of Islamic teachings in Islamic boarding school-based educational institutions for students and graduates are seen from the personal background itself which is heterogeneous, the carrying capacity of all school members and infrastructure.